Aplicação do ePolyScat-D modificado no estudo do espalhamento de elétrons por moléculas poliatômicas - Araújo, Nilton Fagner de Oliveira (2024)
This work presents a theoretical investigation on electron interactions with five molecules: ethylene glycol (ETG), dimethyl peroxide (DMP), hydrogen peroxide (H2O2), diazene (N2H2), and hydrazine (N2H4). For ETG and DMP, we calculated the elastic scattering cross sections at the 1 - 500 eV energy range. A single resonance was observed (at around 10 eV) in the case of ETG while in DMP the peak at 10 eV was noticed along with an additional peak at 5 eV. For H2O2, the interactions with electrons were investigated considering two conformations: anticlinal (ac) and antiperiplanar (ap). At the end, a similar resonance was observed in both conformations, which was assigned to the O-O bond. Interestingly an energy shift of 1 eV was observed between the resonances computed for each conformer which can be used as a marker to identify the conformation of H2O2 in future experimental investigations. For N2H2 and N2H4, the interactions with electrons were studied considering two configurations of diazene (E and Z). The presence of a permanent dipole moment in the Z conformation significantly influenced the elastic scattering, while the results for N2H4 were closer to those of the Z configuration of N2H2. In addition, a resonance was observed in the case of E-N2H2, being assigned to the N-N bond; such peak was noticed in the cases of the Z configuration of N2H2 and N2H4 possibly (most likely) due to the existence of permanent dipole moments that may mask such feature. This investigation provided unprecedented electron scattering cross sections (at a broad energy range) for the molecules of interest as well as exploration of the interaction dynamics features originating from the electronic scattering with such chemical species.